Perancangan Sistem Informasi Manajemen Berbasis Komputer E-Resto Untuk Transaksi, Laporan Keuangan, Dan Stock Control Di Rumah Makan Saung Pengkolan - Agung Gumilar Prayogi; Budi Praptono (eProceedings of Engineering, 2015)
Saung pengkolan Restaurant is Sundanese restaurant that stood since 1978. Management system that is applied in running the restaurant business is still using conventional or manual systems, these systems are considered less effective and efficient allowing the occurrence of errors in recording sales transactions, expenditures, financial statements. In addition, raw materials is not well controlled. For that made computer-based management information system for transactions, financial reports, and stock control that can assist the management of restaurant do their duties in accordance parts each. The information system is called E – Resto. The development process of E-resto using a software methodology development waterfall method, with UML (Unified Modeling Language) tools to describe the modeling system. In UML are known somes diagrams, including use case diagrams, activity diagrams, class diagrams, sequence diagrams, database systems. Programming language that used is a programming language personal home pagetools (PHP) using the Structured Query Language My Database (MySQL). The test that is used to test this application is based on the ISO 9126 standard by test some of the characteristics for tested the quality a software including aspects of functionality, security, usability, efficiency, maintainability, and portability. E-Resto applications are expected to gives ease in Saung Pengkolan restaurant management process. Keywords: Information Systems, Transactions, Stock Control, Finance, E-Resto